Akad-Akad di dalam Asuransi Syariah - Abdullah, Junaidi (Sharia Faculty Islamic Economic Law Study Department, 2018)
Human life is full of risks. There is a risk of loss, accident and even the risk of death. To prepare for these risks, a sense of security is needed through coverage. These coverage is through Islamic insurance. Sharia Insurance (Ta'min, Takaful or Tadhamun) is an effort to protect and help one another among a number of people / parties through investments in the form of assets and / or tabarru 'which provide a pattern of return to face certain risks through an appropriate contract (agreement) with sharia. The contracts that are attached to Islamic insurance are the contract of contract and tabarru 'contract, while the contract that follows the contract of tijarah and the tabarru contract is the Mudharabah Musytarakah agreement, Mudharabah agreement and Wakalah bil Ujrah agreement.